Spectroscopic Study of Interactions of Metal Complexes, Metal Salts and Amino Acids with Anionic Surfactant Sodium Dodecyl Sulphate (SDS) Using Surfactant-Solute-PAN Dye Ternary Systems - Subhan, M. A.; Rana, M. M.; Sarker, P.; Rahman, M. A. (Journal of Scientific Research, 2016)
The study of micellar behavior of SDS in presence of additives such as metal (Fe, Cu, Co, Zn) phendione complexes, calcium salts and amino acids in aqueous solutions in surfactant-solute-1-(2-pyridylazo)-2-naphthol(PAN) dye ternary systems were carried out by measuring the absorbance of PAN at 470 nm. The complexes [Fe(phendione)3](ClO4)2·2H2O, [Co(phendione)3](ClO4)2·3H2O, and [Cu(phendione)2] (ClO4)2·2H2O, decreased the CMC value of SDS from 8 mM to 0.70 mM, 0.40 mM, and 1.0 mM, respectively. In presence of calcium salts (CaCl2, CaF2, calcium acetate, calcium oxalate·H2O) the CMC of SDS decreased. The study of interaction of amino acids with anionic surfactant SDS provides important information about protein-surfactant and peptide-surfactant interaction in aqueous environment. In the present study glycine, L-alanine, L-valine, L-histidine, L-leucine, L-lysine have been used as additives in SDS aqueous solution which also decreased the CMC of SDS. The thermodynamic parameters for each series were obtained from absorbance versus concentration curves. Among the series more negative values for ?G0mic of SDS are observed for the metal complexes. Amino acids series as well as metal salts show similar negative values for ?G0mic of SDS. Negative values of ?G0mic indicated that the process of micellization is thermodynamically favorable.